THE IMPROVEMENT OF LIFELONG LEARNING IN SAUDI ARABIAN UNIVERSITY FROM INDIVIDUAL LEARNING TO SOCIAL CONSTRUCTIVIST E-LEARNING ENVIRONMENT BASED NEW EDUCATIONAL TECHNOLOGIES - Barhoumi, Chokri; Hamza kabli, Talal bin Hasan (European Scientific Journal, ESJ, 2013)
The design of the instructions based social constructivist online course in Saudi Arabian universities is considered a new instructional technology to integrate in higher education compared to individual behavioural course design. The actual study aim is to improve lifelong learning in Saudi Arabian University through exploring the impact of using an online course design based social collaborative e-learning process on the achievement and attitudes of lifelong learning learners comapred to traditional individual learning. Researchers use the experimental approach to explore this impact. One sample contains an experimental group of 30 learners and an other sample of control group contains 30 learners from lifelong learning class in Taibah University. In order to achieve the object of this study, researchers develop an e-learning process based social constructivist e-learning environment for problems solving and observe its effects on the experimental group. Social electronic e-learning process experimeted in present research is based design of constructivist e-learning environment (Jonassen, 1991) and Vygotsky’s social development theory (Vygotsky, 1978) for problem solving and facilitation of online learning and teaching. The t-test is used to find out difference between the experimental and control group. Results of the experimentation show that there is difference between the experimental group and the control group at 0.05 alpha level in the attitudes of learners toward using social construction of knowledge.